Autoimmune congenital heart block: complex and unusual situations. (February 2016) - Brito-Zerón, P; Izmirly, PM; Ramos-Casals, M; Buyon, JP; Khamashta, MA
Autoimmune congenital heart block (ACHB) is an immune-mediated cardiac disease included among the manifestations collectively referred to as neonatal lupus. The placental transference of maternal Ro/La autoantibodies may damage the conduction tissues during fetal development leading to blocking of signal conduction at the atrioventricular (AV) node in an otherwise structurally normal heart. Irreversible complete AV block is the main cardiac manifestation of ACHB, but some babies may develop endocardial fibroelastosis, valvular insufficiency, and/or frank cardiomyopathies with significantly reduced cardiac function requiring transplant. The severity of ACHB is illustrated by a global mortality rate of 20% and pacemaker rates of at least 64%, often within the first year of life. This review analyses the main complex and/or unusual clinical situations associated with ACHB, including unusual maternal immunological profiles, infrequent maternal autoimmune diseases, cardiac damage unrelated to AV block, fetal invasive management, late complications after birth, risk of congenital heart block (CHB) in ovodonation and in vitro fertilization techniques, the role of maternal features other than autoimmunity, the influence of the birth order or the risk of CHB in twins and triplets.